2004
DOI: 10.1182/blood-2003-07-2299
|View full text |Cite
|
Sign up to set email alerts
|

Association of CBFA2 mutation with decreased platelet PKC-θ and impaired receptor-mediated activation of GPIIb-IIIa and pleckstrin phosphorylation: proteins regulated by CBFA2 play a role in GPIIb-IIIa activation

Abstract: The mechanisms by which agonists activate glycoprotein (GP) IIb-IIIa function remain unclear. We have reported data on a patient with thrombocytopenia and impaired receptor-mediated aggregation, phosphorylation of pleckstrin (a protein kinase C [PKC] substrate), and activation of the GPIIb-IIIa complex. Abnormalities in hematopoietic transcription factors have been associated with thrombocytopenia and platelet dysfunction. To define the molecular mechanisms, we amplified from patient platelet RNA exons 3 to 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
94
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 27 publications
6
94
1
Order By: Relevance
“…Both platelet storage pool deficiency 14 and impaired GPIIbIIIa activation 12 have been described. Importantly, the presence of thrombocytopenia is not mandatory for a diagnosis of FPD/AML, as some affected individuals have displayed normal platelet counts, and could, therefore, escape detection within an affected family.…”
Section: Familial Platelet Disorder With Propensity To Myeloid Malignmentioning
confidence: 99%
“…Both platelet storage pool deficiency 14 and impaired GPIIbIIIa activation 12 have been described. Importantly, the presence of thrombocytopenia is not mandatory for a diagnosis of FPD/AML, as some affected individuals have displayed normal platelet counts, and could, therefore, escape detection within an affected family.…”
Section: Familial Platelet Disorder With Propensity To Myeloid Malignmentioning
confidence: 99%
“…The St. Jude's group has already shown that individualized dosing of methotrexate improves outcome in pediatric ALL. 5 Decreased platelet Mpl receptor in AML1 haplodeficiency: another piece of the puzzle…”
Section: Michel Zwaan Erasmus Mc-sophia Children's Hospitalmentioning
confidence: 99%
“…4 PKC-⑀ cooperates with the transcription factor GATA-1 in the activation of the glycoprotein IIb (GPIIb) promoter. 3 Of particular relevance, platelet PKC-expression (protein and mRNA) has been reported to be decreased in AML1 haplodeficiency, 5 suggesting a potential mechanism for the impaired megakaryopoiesis and platelet production. This PKC deficiency has also been associated with impaired platelet responses to activation, including in protein phosphorylation and activation of GPIIb-IIIa.…”
mentioning
confidence: 99%
“…Genetic and molecular studies reveal that all reported pedigrees of FPD/MM display a mutation in the RUNX1 gene or LOH at the locus. [5][6][7][8][9][10] In this report, we present a Japanese family with FPD/MM and a novel RUNX1 mutation.…”
mentioning
confidence: 99%
“…So far, 13 pedigrees have been reported, mainly in European countries. [5][6][7][8][9][10] Clinically, the disorder is characterized by moderate thrombocytopenia from birth, impaired platelet function and a propensity to develop myeloid malignancies. Genetic and molecular studies reveal that all reported pedigrees of FPD/MM display a mutation in the RUNX1 gene or LOH at the locus.…”
mentioning
confidence: 99%